2006
DOI: 10.1109/tdei.2006.1714928
|View full text |Cite
|
Sign up to set email alerts
|

An explanation of the peculiar behavior of TSDC peaks at Tg: a simple model of entropy relaxation

Abstract: Thermally Stimulated Depolarization Current (TSDC) signals measured in polymers at the glass transition T g often exhibit intricate shapes that much depend on the thermal history and on the non-stationary condition used during experiments. This peculiar behavior is frequently explained in terms of a physical singularity of the molecular motions. We show that this singularity, i.e. unexpected values for activation energy and pre-exponential factor, obtained around T g , result from the misuse of the Arrhenius l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…This shows an incomplete depolarization of poled glasses in all earlier performed TSDC measurements except that reported in ref . Additionally, TSDC studies of polymers have shown the importance of the experiments at temperatures in the T g region. , …”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…This shows an incomplete depolarization of poled glasses in all earlier performed TSDC measurements except that reported in ref . Additionally, TSDC studies of polymers have shown the importance of the experiments at temperatures in the T g region. , …”
Section: Introductionmentioning
confidence: 50%
“…Additionally, TSDC studies of polymers have shown the importance of the experiments at temperatures in the T g region. 16,17 In this paper we report extremely high depolarization currents observed in poled silicate glasses above T g (550−800 °C). The measured currents were found to be 5−6 orders of magnitude higher than the ones reported in the aforementioned TSDC studies of similar glasses below T g (200−500 °C).…”
Section: Introductionmentioning
confidence: 64%